2018
DOI: 10.37237/relay/010120
|View full text |Cite
|
Sign up to set email alerts
|

Adopting and Adapting to New Language Policies in a Self-Access Centre in Japan

Abstract: This paper reports on challenges that the new Self-Access Learning Center (SALC) has faced since it moved in to a new building in 2017, and actions taken by learning advisors as SALC managers. Before moving to the new two-storey building, language policies were decided by SALC managers in collaboration with university staff, students, teachers, and administrators. The first floor is a multilingual space and the second floor is an English-only space. However, since we opened the new SALC, although the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A brief examination of articles published about the Japanese context in JASAL Journal and Studies in Self-Access Learning Journal confirms that a vast majority of self-access language learning literature in Japan focuses on the learning of English, and to a lesser extent, Japanese as a foreign language (JFL). Encouragingly, there is a growing body of work examining language policy in Japanese SALCs, which documents a shift away from English-only policies to ones which promote translanguaging (Adamson & Fujimoto-Adamson, 2012;Imamura, 2018;Thornton, 2018) or a more multilingual focus (Murray & Fujishima, 2016;Wongsarnpigoon & Imamura, 2020, 2021. Looking specifically at student perceptions, Thornton's (2020) investigation into student attitudes to SALC language policy revealed that students in both institutions surveyed were supportive of multiple language use in their SALCs.…”
Section: Lote In Self-access In Japanmentioning
confidence: 99%
“…A brief examination of articles published about the Japanese context in JASAL Journal and Studies in Self-Access Learning Journal confirms that a vast majority of self-access language learning literature in Japan focuses on the learning of English, and to a lesser extent, Japanese as a foreign language (JFL). Encouragingly, there is a growing body of work examining language policy in Japanese SALCs, which documents a shift away from English-only policies to ones which promote translanguaging (Adamson & Fujimoto-Adamson, 2012;Imamura, 2018;Thornton, 2018) or a more multilingual focus (Murray & Fujishima, 2016;Wongsarnpigoon & Imamura, 2020, 2021. Looking specifically at student perceptions, Thornton's (2020) investigation into student attitudes to SALC language policy revealed that students in both institutions surveyed were supportive of multiple language use in their SALCs.…”
Section: Lote In Self-access In Japanmentioning
confidence: 99%